The causal relationship between gut microbiota and leukemia: a two-sample Mendelian randomization study - Chen, Guanjun; Kuang, Zheshu; Li, Fan; Li, Jianchang (Frontiers in Microbiology, 2023)
Background The association between gut microbiota and leukemia has been established, but the causal relationship between the two remains unclear. Methods A bidirectional two-sample Mendelian randomization (MR) was used to analyze the causal relationship between gut microbiota and leukemia. Microbiome data (n = 14,306) and leukemia (n = 1,145) data were both sourced from European populations. Single nucleotide polymorphisms (SNPs) were selected as instrumental variables based on several criteria. We employed various MR methods, such as the inverse variance weighted (IVW) method, to evaluate the causal effect between exposure and outcomes and conducted sensitivity analyses to validate the heterogeneity and pleiotropy of the instrumental variables. Results 5,742 qualified instrumental variables were included. In the primary MR results, a total of 10 gut microbial taxa were associated with leukemia risk. Genus Blautia and genus Lactococcus are risk factors for acute lymphoblastic leukemia [genus Blautia odds ratio (OR): 1.643, 95% confidence interval (CI): 1.592 1.695, Adjusted p < 0.001; genus Lactococcus OR: 2.152, 95% CI: 1.447 3.199, Adjusted p = 0.011]. Genus Rikenellaceae RC9 gut group, genus Anaerostipes, genus Slackia, and genus Lachnospiraceae ND3007 group are risk factors for acute myeloid leukemia [genus Rikenellaceae RC9 gut group OR: 1.964, 95% CI: 1.573 2.453, Adjusted p < 0.001; genus Anaerostipes OR: 2.515, 95% CI: 1.503 4.209, Adjusted p = 0.017; genus Slackia OR: 2.553, 95% CI: 1.481 4.401, Adjusted p = 0.022; genus Lachnospiraceae ND3007 group OR: 3.417, 95% CI: 1.960 5.959, Adjusted p = 0.001]. Genus Ruminococcaceae UCG011 and genus Ruminococcaceae UCG014 were risk factors for chronic myeloid leukemia (genus Ruminococcaceae UCG011 OR: 2.010, 95% CI: 1.363 2.963, Adjusted p = 0.044; genus Ruminococcaceae UCG014 OR: 3.101, 95% CI: 1.626 5.915, Adjusted p = 0.044). Genus Slackia was a protective factor for acute lymphoblastic leukemia (genus Slackia OR: 0.166, 95% CI: 0.062 0.443, Adjusted p = 0.017). Family Acidaminococcaceae was a protective factor for acute myeloid leukemia (family Acidaminococcaceae OR: 0.208, 95% CI: 0.120 0.361, Adjusted p < 0.001). Genus Desulfovibrio was a protective factor for chronic lymphoblastic leukemia (genus Desulfovibrio OR: 0.581, 95% CI: 0.440 0.768, Adjusted p = 0.020). Sensitivity analysis revealed no heterogeneity or pleiotropy between SNPs. Conclusion This study revealed the causal relationship between the gut microbiota and leukemia, and identified potential pathogenic bacteria and probiotic taxa associated with the onset of leukemia. This research may aid in the early detection of various types of leukemia and offer a new direction for the prevention and treatment of leukemia.